Impact of Tax Implementation on Fintech P2P Loans in Indonesia - Stanley, Nicklaus; Kohardinata, Cliff (EconBank: Journal of Economics and Banking, 2023)
This research paper aims to examine the impact of tax implementation on the number of P2P loan recipients and the amount of P2P loan disbursement in fintech industry of Indonesia. This empirical study is based on the number of accounts and loan data acquired from one of Indonesia’s government agencies – the Financial Services Authority (OJK) from February 2022 to April 2022 and June 2022 to August 2022 that are analyzed using various tests such as Skewness-Kurtosis Test, the variance ratio test, and t-test. The results show that tax implementation does not significantly affect the number of P2P loan recipients and the amount of P2P loan disbursement. This is because fintech offers greater benefits than traditional banks, such as convenience, time-saving, more access to financial products, and better security measures. The limited amount of available data and the number of provinces available become the limitation of the study to obtain optimum results.